Analysis Of Use Sea Sand as A Fine Aggregate Replacement To Strong Press Concrete - Fachrul Arya Sanjaya; Sapto Budy Wasono; Diah Ayu Restuti Wulandari (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
Concrete is a composite building material made from a combination of aggregate and cement. The limitation of concrete material, in this case, is a fine aggregate (river sand). The utilization of sea sand as an alternative to fine aggregate in the manufacture of concrete is motivated by the availability of sea sand in nature in very large quantities. This study aims to determine the comparison and how much the compressive strength of concrete produced when using sea sand. The test was carried out when the specimens were 7, 14, and 28 days old with the specimens used in this study were concrete cylinders with a diameter of 15 cm and a height of 30 cm. The results showed that the use of sea sand as a substitute for fine aggregate showed an average compressive strength in 7 days of 18.86 MPa, an average compressive strength of 14 days of 25.52 MPa, an average compressive strength of 28 days of 29.00 MPa. Then for the average compressive strength value of the use of river sand in 7 days is 17.17 MPa, the average compressive strength of 14 days is 23.24 MPa, the average compressive strength of 28 days is 26.41 MPa.